2019
DOI: 10.3802/jgo.2019.30.e39
|View full text |Cite
|
Sign up to set email alerts
|

Asian Society of Gynecologic Oncology International Workshop 2018

Abstract: The Asian Society of Gynecologic Oncology International Workshop 2018 on gynecologic oncology was held in the Ajou University Hospital, Suwon, Korea on the 24th to 25th August 2018. The workshop was an opportunity for Asian doctors to discuss the latest findings of gynecologic cancer, including cervical, ovarian, and endometrial cancers, as well as the future of fertility-sparing treatments, minimally invasive/radical/debulking surgery, radiotherapy, chemotherapy, targeted therapy, and immunotherapy. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 100 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Also, in patients with any one intermediate risk factor, the additional benefit of chemoradiation could not be demonstrated in the STARS trial (Sequential Chemoradiation vs Concurrent Chemoradiation or Radiation Alone in Adjuvant Treatment After Hysterectomy for Cervical Cancer), although sequential chemoradiation was superior to radiation alone. Presently, GOG 263/KROG1008 is testing the role of chemoradiation 22. Unlike the treatment intensification strategies adopted in the intermediate risk group in the trials mentioned above, the CERVANTES trial (NCT 04989647) is testing the omission of radiation 23.…”
Section: Role Of Adjuvant Systemic Chemotherapy In the Postoperative ...mentioning
confidence: 99%
“…Also, in patients with any one intermediate risk factor, the additional benefit of chemoradiation could not be demonstrated in the STARS trial (Sequential Chemoradiation vs Concurrent Chemoradiation or Radiation Alone in Adjuvant Treatment After Hysterectomy for Cervical Cancer), although sequential chemoradiation was superior to radiation alone. Presently, GOG 263/KROG1008 is testing the role of chemoradiation 22. Unlike the treatment intensification strategies adopted in the intermediate risk group in the trials mentioned above, the CERVANTES trial (NCT 04989647) is testing the omission of radiation 23.…”
Section: Role Of Adjuvant Systemic Chemotherapy In the Postoperative ...mentioning
confidence: 99%
“…Minor variations of fertility-sparing treatment by other gynecologic oncology societies are primarily in regards to follow-up biopsy; the Japan Society of Gynecologic Oncology recommends endometrial biopsy at 3 months following progestin treatment [101], and the Korean Society of Gynecologic Oncology recommends endometrial biopsy at 3-6 month for fertilitysparing treatment of grade 1 endometrioid tumors confined to the endometrium [102]. In addition, the Gynecologic Oncology Branch of the Chinese Medical Association requires patients to be under the age of 40 and progesterone-receptor positive to be considered for fertility-sparing therapy [103]. • Patients who wish to conceive following a complete response should be advised to pursue pregnancy earlier and consider ART to improve success rates.…”
Section: Guidelines and Recommendationsmentioning
confidence: 99%
“…The aim of this symposium was to maintain a good relationship among Asian countries to encourage international collaborations through clinical trials for gynecologic cancer. Prof. Tae-Wook Kong (Ajou University School of Medicine, Suwon, Republic of Korea) presented oncologic outcomes of minimally invasive radical hysterectomy after using parametrial invasion criteria on magnetic resonance imaging and vaginal colpotomy and concluded that the operation should be performed more cautiously, in optimal surgical candidates, to obtain en bloc resection without positive margin and tumor spillage, using vaginal colpotomy after CO 2 evacuation [7][8][9]. Prof. Kung-Liahng Wang (President of the Taiwanese Gynecologic Oncology Group) presented updates regarding the controversies of laparoscopic or robotic surgeries for cervical cancer, and discussed the disagreement in the literature regarding the effect of utilizing laparoscopic or robotic surgery versus traditional laparotomy regarding the risk of decreasing survival among patients with cervical cancers [10,11].…”
Section: Jsgo Annual Meeting 2019mentioning
confidence: 99%
“…He presented the recent activities of KGOG, such as the ongoing joint research with Japanese Gynecologic Oncology Group (JGOG), including KGOG3011/GCIG/JGOG3017, KGOG3026/JGOG3019/GOTIC-001, and KGOG3035/JGOG3020 [34], as well as the KGOG-JGOG Young Doctors' Meeting and the regular exchange program of young medical scientists between KGOG and JGOG. Prof. Seung Cheol Kim (President of the Korean Society of Gynecologic Oncology [KSGO]) presented a history of KSGO and the Journal of Gynecologic Oncology ( JGO ), especially the recent relationship with JSGO [567].…”
mentioning
confidence: 99%